The effects of private damage claims on cartel activity: Experimental evidence - Olivia Bodnar; Melinda Fremerey; Hans-Theo Normann; Jannika Leonie Schad (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
Private damage claims against cartels may have negative effects on leniency: whereas whistleblowers obtain full immunity regarding the public cartel fines, they have no or only restricted protection against private third-party damage claims. This may stabilize cartels. We run an experiment to study this issue. Firms choose whether to join a cartel, may apply for leniency afterwards, and then potentially face private damages. We find that the implementation of private damage claims reduces cartel formation but makes cartels indeed more stable. The negative effect of damages is avoided in a novel setting where the whistleblower is also protected from damages.
Keywords: C90; L41; L44; 330; Private damage claims; cartel stability; laboratory experiment; leniency